Do newspaper articles on card fraud affect debit card usage? - Anneke Kosse (European Central Bank (ECB), 2011)
This paper investigates the impact of newspaper publications about debit card skimming fraud on debit card usage in the Netherlands using daily information from January 1st 2005 to December 31st 2008. Time-series analyses are employed to assess the daily fluctuations in aggregate debit card usage. The results show that newspaper articles that somehow make mention of the phenomenon of skimming fraud significantly affect the number of debit card payments. The direction of the effect depends on the type of skimming fraud addressed. Newspaper articles on fraud at points-of-sale (POS) and ticket machines depress the number of debit card payments. News on ATM fraud, by contrast, has a positive effect on debit card payments. This indicates that the temporarily created fear for using the debit card at the ATM is not automatically translated into fear for using the debit card at the POS. Instead, ATMs and POS terminals are perceived as substitutes. Although significant, all media effects found are relatively small in comparison with other factors such as calendar and holiday effects and daily rainfall. Moreover, the effects only last for one day, with consumers immediately reverting back to their regular payment behaviour. This corresponds to earlier results found in other research fields and suggests that consumers' confidence in the debit card is relatively sturdy and not easily affected. Moreover, it might be an indication of consumers having a short memory when it comes to newspaper articles.
Keywords: C22; C23; D12; E21; 330; Debit card; fraud; media communication; payment behaviour; Kreditkarte; Betrug; Mediennutzung; Öffentliche Meinung; Konsumentenverhalten; Niederlande